2019
DOI: 10.3389/fphar.2019.01385
|View full text |Cite
|
Sign up to set email alerts
|

The Abilities of Salidroside on Ameliorating Inflammation, Skewing the Imbalanced Nucleotide Oligomerization Domain-Like Receptor Family Pyrin Domain Containing 3/Autophagy, and Maintaining Intestinal Barrier Are Profitable in Colitis

Abstract: Salidroside (Sal), as a major glycoside extracted from Rhodiola rosea L., has exhibited its mighty anti-aging, anti-oxidant, anti-cancer, anti-inflammation, and neuroprotective effects in many diseases. Recently, it has showed its protective effect in colitis mice by activating the SIRT1/FoxOs pathway. Whereas, it is not known whether Sal has other protective mechanisms on dextran sulfate sodium (DSS)-induced colitis in mice. In this study, we investigated the protective effects and mechanisms of Sal on DSS-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Similarly, SAL administration improved mechanical ventilation-induced lung injury in mice through the Sirt1-dependent inhibition of the NLRP3 inflammasome [ 40 ]. In dextran sulfate sodium-induced ulcerative colitis models, the protective effects of SAL were in part dependent on its inhibitory effects on the NLRP3 inflammasome [ 41 ]. Moreover, SAL has been shown to regulate the NLRP3 inflammasome through the TXNIP-NLRP3 pathway, providing protection against high glucose exposure, due to the accumulation of the extracellular matrix in glomerular mesangial cells [ 42 ] or through insulin resistance in hepatocytes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, SAL administration improved mechanical ventilation-induced lung injury in mice through the Sirt1-dependent inhibition of the NLRP3 inflammasome [ 40 ]. In dextran sulfate sodium-induced ulcerative colitis models, the protective effects of SAL were in part dependent on its inhibitory effects on the NLRP3 inflammasome [ 41 ]. Moreover, SAL has been shown to regulate the NLRP3 inflammasome through the TXNIP-NLRP3 pathway, providing protection against high glucose exposure, due to the accumulation of the extracellular matrix in glomerular mesangial cells [ 42 ] or through insulin resistance in hepatocytes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has revealed that SAL provides neuroprotection by modulating mitochondrial biogenesis and microglial polarization ( Barhwal et al, 2015 ; Liu et al, 2018 ). Notably, SAL exhibits significant anti-inflammatory effects in multiple diseases, such as osteoarthritis ( Chen et al, 2019 ), colitis ( Liu et al, 2019 ), skeletal muscle atrophy ( Huang et al, 2019 ), renal interstitial fibrosis, ( Li et al, 2019 ) and CNS diseases ( Liu et al, 2018 ; Wang et al, 2018 ). Furthermore, recent findings have suggested that SAL alleviates liver injury by maintaining the balance of the gut microbiota ( Yuan et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…SAL reduced obesity, abnormal blood glucose and liver lipid deposition in NAFLD mouse model by regulating ROS and AMPK-dependent TXNIP/NLRP3 pathways (201). Moreover, SAL also showed therapeutic potential in UC and CCl 4 -induced liver injury models (202,203). Dihydromyricetin (DHM) is a polyphenol which isolates from Ampelopsis grossedentata.…”
Section: Phytochemicalsmentioning
confidence: 99%